PREGNANCY AFTER KIDNEY TRANSPLANTATION AS A CLINICAL CHALLENGE: A NARRATIVE REVIEW - Maja Witek; Izabela Migdał; Justyna Polko; Zuzanna Jeziorska; Bartosz Szymajda; Tomasz Horodniczy; Zuzanna Galicka; Jakub Artur Czapkiewicz; Weronika Kwaśnica; Katarzyna Raczek (Archiv Euromedica, 2026)
Background Pregnancy after kidney transplantation has become a realistic reproductive option owing to advances in transplantation, immunosuppressive therapy, and multidisciplinary care. However, kidney transplant recipients remain at increased risk of maternal, fetal, neonatal, and graft related complications, requiring careful preconception assessment and close monitoring throughout pregnancy. Aims The aim of this review is to summarize current evidence regarding maternal, fetal, neonatal, and graft related outcomes of pregnancy after kidney transplantation. Particular attention is paid to preconception counseling, immunosuppressive therapy, pregnancy monitoring, multidisciplinary management, and long term maternal, graft, and offspring outcomes. Materials and Methods This narrative review was conducted in accordance with the SANRA recommendations. Literature indexed in PubMed and Google Scholar and published between 2019 and July 2026 was analyzed. Clinical guidelines, registry analyses, systematic reviews, meta analyses, observational cohort studies, and retrospective studies were included. Ultimately, forty-three publications were incorporated into the review. Results Pregnancy after kidney transplantation is associated with an increased risk of hypertension, preeclampsia, gestational diabetes mellitus, preterm delivery, neonatal complications, and graft related complications. Reported live birth rates range from approximately 70% to 90%, whereas preeclampsia affects 24 to 38% of pregnancies and preterm delivery occurs in 40 to 60% of cases. More favourable outcomes are associated with stable graft function before conception, minimal proteinuria, well controlled blood pressure, absence of recent rejection, and planned pregnancy. Calcineurin inhibitors, azathioprine, and low dose corticosteroids are generally considered compatible with pregnancy, whereas mycophenolate mofetil is contraindicated because of its teratogenic effects. Conclusions Pregnancy after kidney transplantation is feasible in carefully selected women with stable graft function. However, the risks of maternal, neonatal, and graft related complications remain higher than in the general population. Successful management requires preconception counseling, adjustment and monitoring of immunosuppressive therapy, and coordinated multidisciplinary care. Evidence regarding long term maternal renal outcomes and developmental outcomes in offspring remains limited.